Identifying Factors Affecting the Imbalance of the Human Development Index between the Provinces of the Country Emphasizing the Ground Theory Method - Leila kalantari dehaghi; Iraj Saei Arasi; Sasan Vadiea (توسعه اجتماعی)
Since development is not a multi-dimensional phenomenon based on the economy and a developed country must be developed in all aspects, an important part of it is the human development index. The human development index appeared as one of the important development indicators in the development program and caused the factors affecting the imbalance of the human development index level to be investigated in this program. The purpose of this research is to discover the factors affecting the imbalance of the human development index level among the provinces of the country and to design the paradigm of the human development index. Using descriptive statistics, the comparison of human development indicators between provinces was made, then qualitative data obtained from expert interviews were analyzed with the help of Maxqda software, and the paradigm of imbalance of the level of human development index was achieved. Five factors that are the cause of the imbalance of the human development index have been identified, which include: educational facilities, health and welfare facilities, inappropriate planning, unbalanced development and economic poverty, so these factors lead to the formation and realization of the balance in human development between the provinces. They will be. Human indicators are unevenly distributed in the country and the border provinces often have less of these indicators and its focus is in Tehran. Relying on a single-product economy, lack of security, isolation in global interactions, lack of a strategic plan are among the significant factors in the lack of human development in the country.